Structure And Properties Of Polypropylene Filled With Metal Oxide Fillers - TojiyevP.J; TuraevH.Kh; NuralievG.T; DzhalilovA.T (Zien Journals, 2022)
Background of the problem. Polyolefins (PO) are the most large-tonnage, available and in demand from the entire range of polymers produced by the industry. Therefore, the search for technical solutions aimed at simplifying the processing of polyolefins and the creation of new types of composite materials based on them is an urgent task
Keywords: polypropylene; metal oxides; atomic force microscopy; physicochemical